2001
DOI: 10.1159/000063003
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hypopharyngeal Leiomyosarcoma

Abstract: Squamous cell carcinoma is the most common malignant neoplasm in the hypopharynx. Other types of malignant neoplasm are rare. Leiomyosarcomas are commonly found in the alimentary tract and the uterus. Only 6 cases of hypopharyngeal leiomyosarcoma have been reported in the past. We report here the seventh case of this rare tumor, which arose from the piriform sinus in a 69-year-old man. The tumor was completely resected, and the pharynx and larynx were reconstructed. The patient remains free of recurrence 25 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Extensive review of modern literature showed that there were only less than 10 cases of hypopharyngeal leiomyosarcoma reported; adding to the rarity of the present case. 2 The etiological factors which play in the genesis of this rare malignancy are still unclear. Unlike the squamous cell carcinomas of the larynx which have smoking and alcohol as an important etiological component, their role in leiomyosarcoma larynx is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive review of modern literature showed that there were only less than 10 cases of hypopharyngeal leiomyosarcoma reported; adding to the rarity of the present case. 2 The etiological factors which play in the genesis of this rare malignancy are still unclear. Unlike the squamous cell carcinomas of the larynx which have smoking and alcohol as an important etiological component, their role in leiomyosarcoma larynx is still uncertain.…”
Section: Discussionmentioning
confidence: 99%